Upaya Meningkatkan Minat Belajar Siswa Kelas IV Pada Pembelajaran IPS dengan Menggunakan Media Gambar di SDK Roworeke 2 - Raji, Manggu Ngguna; Korosando, Fransiskus (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to describe efforts to increase the learning interest of fourth grade students in learning social studies using image media at SDK Roworeke 2 East Ende. This type of research is qualitative, namely the researcher describes how to increase the learning interest of fourth grade students in social studies learning using image media at SDK Roworeke 2 Ende Timur through in-depth interviews with research information supported by observation and documentation processes. The research subjects were the principal, class IV teacher and 4 class IV students. The results of the research show that the teacher's strategy in using image media can increase the learning interest of fourth grade students learning social studies by using image media at SDK Roworeke 2 East Ende, namely; adapting the material to the images that will be used, designing the image media that will be used considering the limitations of the media, compiling steps in using image media, adjusting learning steps based on lesson plans, references and learning objectives that have been prepared previously